Application of Servant Leadership Style With Ki Hajar Dewantara Philosophy Approach - Gunawan, Ahmad; Hisniati, Sally Badriya; ed, Sarwo (DPPM Universitas Pelita Bangsa, 2023)
This study discusses the application of servant leadership style with the philosophical approach of Ki Hajar Dewantara. The servant leadership style emphasizes service, empathy, and subordinate development, while the Ki Hajar Dewantara philosophical approach refers to holistic educational principles and prioritizes a balance between intellectual and emotional intelligence. The purpose of this study is to analyze how the application of servant leadership style inspired by the philosophy of Ki Hajar Dewantara can have a positive impact on the work environment or organization. To determine the effectiveness of servant leadership style in the implications of lecturer closeness with students as learners; To find out the success of educational institutions in implementing using the application of servant leadership with the correlation of the philosophy of Ki Hajar Dewantara. This research uses qualitative methods with a literature study approach and contextual analysis. Based on the available literature, servant leadership style is applied through developing strong relationships between leaders and subordinates, listening with empathy, giving praise and recognition, and providing personal development opportunities. The philosophy of Ki Hajar Dewantara is also analyzed to see how the concept of holistic education and character building can be adapted in the context of servant leadership.The results of the analysis show that the application of servant leadership style with the Ki Hajar Dewantara philosophical approach can strengthen bonds in the team, increase subordinate satisfaction and motivation, and encourage overall individual growth. The connection between servant leadership aspects and the principles of Ki Hajar Dewantara creates an inclusive, inspiring, and effective work environment.